Assessing educational leadership: a competence-complexity based test - Parreira, A.; Pestana, M. H.; Oliveira, P. (Ensaio: Avaliação e Políticas Públicas em Educação, 2018)
This study is focused on the validation of a leadership test, based on a complex model of leadership skills, as a tool for assessing teacher’s educational competence, viewed as important in conduting adolescent and adult learning classes. Its specific purpose is to establish the norms and interpretation criteria for the test, in educational contexts. The model highlights the skills for leadership effectiveness, in a definite cultural setting, the Academy of East Timor National Police, viewing leadership as an essential way of steering human systems. The postulates of the model hypothesize the positivity of leadership as a result from an appropriate combination of power and information, while executing the fundamental activities of dinamizing and controlling the performance and results of the learning ativities. The test was applied to a sample of trainees in an educational military context, the Academy of East Timor National Police. The results of their evaluations on each competence for leadership effectiveness were valid and reliable. Nevertheless, the authors plan to test this tool in other specific contexts, in order to complete the evaluation of the leadership complex set of competences required by educational contexts.